POLA KOMUNIKASI KOMUNITAS VESPA DALAM MEMPERTAHANKAN SOLIDARITAS KELOMPOK (Studi pada KUTU Vespa Region Bali) - Ayu Megasari, Ni Ketut Diana; Ramaswati Purnawan, Ni Luh; Pradipta, Ade Devia (E-Jurnal Medium, 2017)
ABSTRAK The goal of this research is to describe and to explain the internal communication pattern of KUTU Vespa Bali’s Region in keep their group’s solidarity. This research is using descriptive qualitative approachment. The informan is selected by using purposive and snowball technique. The data is obtained by interview, direct observation and documentation study. The technique of analyzing the data that used in this research through several steps that was data reduction, data presentation and conclution. The result of this research shows that KUTU Vespa Bali’s Region using two kind of communication patterns. First is wheel communication pattern in which occur when they hold a formal and structural activity. Second is all channels communication pattern that occur when they hold on informal activity. The all channels communication pattern stimulate the brotherhood’s feel and begin more tighten their solidarity. Keywords : Communication Pattern, Vespa Community, Solidarity